Do payroll tax cuts raise youth employment? - Johan Egebark; Niklas Kaunitz (Research Institute of Industrial Economics (IFN), 2014)
In 2007, the Swedish employer-paid payroll tax was cut on a large scale for young workers, substantially reducing labor costs for this group. Using Difference-in- Differences paired with exact matching, we estimate a small impact, both on employment and on wages, implying a labor demand elasticity for young workers at around 􀀀0:31. Since the tax reduction applied also to existing employments, the cost of the reform was sizable, and the estimated cost per created job is at more than four times that of directly hiring workers at the average wage. Hence, we conclude that payroll tax cuts are an ineffcient way to boost employment for young individuals.
Keywords: H25; H32; J23; J38; J68; 330; Youth unemployment; Payroll tax; Tax subsidy; Labor costs; Exact matching